Description of female adult and praniza larva of Tenerognathia visus Tanaka, 2005 (Crustacea; Isopoda; Gnathiidae) with notes on mating behavior - Ota, Yuzo (Zootaxa, 2019)
Male adults of gnathiid isopods (Crustacea; Isopoda; Gnathiidae) have remarkably developed rectangular-shaped cephalosomes and mandibles in most species. Tenerognathia visus Tanaka, 2005 belongs to a monospecific genus having remarkable characters in male morphology; reduced mandibles and large eyes occupying the whole of an elliptical cephalosome. The original description of T. visus is based on male adult specimens from coral rubble. This study found adult males and their larvae of T. visus attracted by light. Furthermore, specimens of female adults were observed by laboratory rearing of praniza larvae. In this study, morphologies of larvae and female adults of T. visus are described and notes on mating behavior in a laboratory aquarium are provided.